QPSK, IJF-OQPSK and XPSK a comparative evaluation - Castillo, Rajah K.J.C. (1997)
This thesis consists of the modeling, simulation and evaluation of QPS, IJF0OQPSK and XPSK modulation techniques given different conditions. The different modulators and demodulators were modeled. The bit error rate (BER) performance degradation of QPSK, IJF-OQPSK and XPSK due to channel bandlimiting and nonlinearities were determined through simulation using Omnisys. The effects of different detection filters on the BER performance of QPSK, IJF-OQPSK and XPSK were also studied. The effect of varying nonlinearities on the BER performance of the different modulation schemes were also simulated. Results of the study showed that QPSK, IJF-OQPSK and XPSK have similar BER performance under ideal channel conditions. The BER performance of QPSK and IJF-OQPSK modulation becomes degraded when passed through channel nonlinearities while XPSK modulation is not effected by channel nonlinearities. A channel with a roll-off factor n of 0.5 gives a better BER performance over n= 1.0 and 0.3 in a linear channel. Passive filter detection is superior over integrate and dump (I%D) detection in bandlimited linear and nonlinear channels. A 3rd order chebychev detection filter performs slightly better than a 3rd order butterworth filter.
Computer print-out.
Thesis (M. S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Digital modulation; Digital communications; Phase modulation; Phase shift keying; Telecommunication systems